The Effect of Financial Targets and Audit Committee on Fraudulent Financial Reporting at PT. Pertamina - Nurfadilah, Gia; Mahadianto, Moh. Yudi (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2025)
This study investigates the influence of financial targets and the audit committee's structure on the likelihood of fraudulent financial reporting, using PT Pertamina (Persero), a major Indonesian state-owned enterprise (SOE), as a case study. Drawing on agency theory and public sector governance perspectives, the research employs a descriptive case analysis supported by limited quantitative data from 2019 to 2023. Fraudulent reporting is proxied using the Beneish M-Score, while financial targets are measured via return on assets (ROA), and audit committee performance is proxied by committee size. Despite regression tests suggesting a positive relationship between financial targets and fraud indicators, the reliability of statistical findings is constrained by the minimal data points and static variance in the dependent variable. The audit committee's role was found to be statistically insignificant, which calls into question the current composition and oversight function within SOEs. This study recommends revising fraud detection models for public enterprises and strengthening governance mechanisms, particularly by enhancing the competence, independence, and regulatory supervision of audit committees. Future research should broaden the scope by incorporating multiple SOEs, employing richer governance indicators, and utilizing mixed-methods designs to yield more valid and generalizable insights.